The adolescents having substance disorder applying to treatment çenter via probation, health policy and family: similar? different? - Yüncü, Zeki; Başay, Ömer; Altıntoprak, Ender; Coşkunol, Hakan; A. Akgür, Serap; Aydın, Cahide (Journal of Dependence, 2010)
Objective: Sentencing the children, who are substance abusers, with heavy imprisonment will not be an effective way of protection. Taking on the children’s substance abuse matters by the social security and help associations rather than the criminal courts will be a healthy attitude. Probation (P) and the health policy (HP) are among these practices. The similarities and the differences of the cases applying via P, HP and FS (family support) have been assessed in this study. Methods: The file records of the cases applied to an addiction center towards the children and adolescents having substance disorder, between January 2005 and December 2007 have been reviewed. It has been determined that 326 cases have applied to the center in this period. It has been determined that 16 of these cases P (4.9 %) scope and 16 of them have been assessed within the HP (4.9 %) scope. The cases, who applied via family (n=16) have been appointed randomly. SPSS 13.0 program has been used for the statistical assessment. Results: It has been found that the differences among the groups are statistically meaningful in terms of onset age and the early onset age belongs to the cases having FS (p<0.05). It has been determined that there is a statistically meaningful difference among the groups in terms of marihuana and inhalant abuse (p<0.05). It has been determined that 31.2 % of the cases applied through HP have been under treatment in other association before (p<0.05). It has also been determined that the differences among the cases statistically meaningful in terms of existence of street life, behaviors those may cause criminal problems and work life (p<0.05). Conclusion: The health services should be structured by guarding the substance abuse in children. With P and HP practices it has been possible to reach a group, who denies the substance abuse, who has not been subject to any treatment or continued the treatment but inclined to the criminal behavior.